2012
DOI: 10.1016/j.jcrs.2012.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous increases in multiple proinflammatory cytokines in the aqueous humor in pseudophakic glaucomatous eyes

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 36 publications
1
64
1
2
Order By: Relevance
“…9,15,[20][21][22][23] To assess the influence of previous ocular surgeries on the cytokine levels in AqH, we conducted a correlation analysis between the two (Table 3). The number of previous ocular surgeries was strongly positively correlated with the following cytokine levels: IL-1a (r ¼ 0.47, P < 0.0001), IL-4 (r ¼ 0.46, P < 0.0001), IL-6 (r ¼ 0.50, P < 0.0001), IL-8 (r ¼ 0.50, P < 0.0001), IL-10 (r ¼ 0.48, P < 0.0001), IL-13 (r ¼ 0.38, P < 0.0001), IL-17A (r ¼ 0.32, P < 0.0001), MIP-1b (r ¼ 0.42, P < 0.0001), sICAM-1 (r ¼ 0.42, P < 0.0001), MCP-1 (r ¼ 0.26, P ¼ 0.001), P-selectin (r ¼ 0.26, P ¼ 0.001), and E-selectin (r ¼ 0.29, P ¼ 0.0002).…”
Section: Correlations Between Cytokine Levels In Aqh and The Number Omentioning
confidence: 99%
See 1 more Smart Citation
“…9,15,[20][21][22][23] To assess the influence of previous ocular surgeries on the cytokine levels in AqH, we conducted a correlation analysis between the two (Table 3). The number of previous ocular surgeries was strongly positively correlated with the following cytokine levels: IL-1a (r ¼ 0.47, P < 0.0001), IL-4 (r ¼ 0.46, P < 0.0001), IL-6 (r ¼ 0.50, P < 0.0001), IL-8 (r ¼ 0.50, P < 0.0001), IL-10 (r ¼ 0.48, P < 0.0001), IL-13 (r ¼ 0.38, P < 0.0001), IL-17A (r ¼ 0.32, P < 0.0001), MIP-1b (r ¼ 0.42, P < 0.0001), sICAM-1 (r ¼ 0.42, P < 0.0001), MCP-1 (r ¼ 0.26, P ¼ 0.001), P-selectin (r ¼ 0.26, P ¼ 0.001), and E-selectin (r ¼ 0.29, P ¼ 0.0002).…”
Section: Correlations Between Cytokine Levels In Aqh and The Number Omentioning
confidence: 99%
“…We confirmed the significant correlation between some cytokine levels in AqH and the number of previous surgeries, which is in line with previous studies. 20,22,23 However, although the number of the previous surgeries was small (0.5 6 0.5, ranging from 0 to 1) in eyes with a low ECD, the aqueous levels of IL-1a, IL-8, IL-17A, TNFa, GM-CSF, MIP-1a, IFN-c, and E-selectin were significantly elevated in eyes with a low ECD, compared with healthy controls, suggesting that ocular surgeries were not the solitary factor responsible for the elevation of cytokine levels. Further studies using multivariate analyses are necessary to assess clinical factors associated with elevated levels of cytokines and decreases in ECD.…”
Section: Figurementioning
confidence: 99%
“…Anatomically, the aqueous humor (AqH) is present between the corneal endothelium and the iris, and it has been reported that inflammatory cytokines in the AqH increase during various pathological processes. [15][16][17][18] In an in vitro study, a combination of proinflammatory cytokines synergistically induced the apoptosis of corneal endothelial cells. 19 We recently showed that inflammatory cytokine levels were elevated in the AqH of eyes with bullous keratopathy and reduced ECDs, 20 and that iris damage was associated with an elevation in aqueous cytokine levels.…”
mentioning
confidence: 99%
“…6 In our previous studies using aqueous humor samples obtained from the patients with glaucoma, elevated levels of MCP-1 were found in pseudophakic eyes after cataract surgery. 8 In addition, a previous study evaluating aqueous MCP-1 levels in the same patients before and after phacoemulsification also demonstrated increased MCP-1 levels postoperatively in cataract eyes (nonglaucomatous eyes; Kawai M, et al IOVS 2012;53:ARVO EAbstract 2503). Interestingly, the postsurgical percentage change from the baseline aqueous MCP-1 level was negatively correlated with the baseline of IOP in the study.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, our previous study showed that aqueous humor obtained from eyes with open-angle glaucoma contained increased monocyte chemoattractant protein-1 (MCP-1)/CC chemokine ligand 2 and IL-8 levels after phacoemulsification. 8 In another study, we also observed elevated MCP-1 and IL-8 levels in the aqueous humor obtained from non-glaucomatous eyes after phacoemulsification compared with that before surgery (Kawai M, et al IOVS 2012;53:ARVO E-Abstract 2503). Regarding the effects of IL-8 on the conventional outflow route, IL-8 decreases the resistance of the Schlemm's canal epithelial (SCE) cell sheet.…”
mentioning
confidence: 81%